The Burden and Antibiotic Sensitivity of Salmonella Non-Typhi and Shigella Related Bloody Diarrhea in Children - Abir Rashid Al Sinani; Tawfiq Taki Al Lawati; Hajar Musabah Al Saadi; Aamera Al Majrafi (Oman Medical Journal)
Objectives: We sought to report the frequency of non-typhoidal Salmonella (SNT) and Shigella spp. diarrhea and the antibiotic sensitivity in children. Methods: We conducted a retrospective study of children with bloody diarrhea seen at Rustaq Hospital between 1 June 2019 and 31 June 2023. We collected data related to demographic characteristics, symptoms, blood investigations, stool bacterial culture, and antimicrobial sensitivity. Stool samples were tested for Salmonella and Shigella growth. Results: Out of 1160 children with diarrhea, 153 (13.2%) had bloody diarrhea of which 129 (84.3%) were under five. Ninety-two (60.1%) children were positive for either Salmonella or Shigella. Among the positive cultures, 58 (63.0%) children had SNT, while 34 (37.0%) had Shigella infection. Three children had bacteremia, all under one year old. SNT demonstrated high sensitivity primarily to ceftriaxone (n = 41; 70.7%), ampicillin (n = 53; 91.4%), and ciprofloxacin (n = 54; 93.1%). In contrast, Shigella showed high resistance to ceftriaxone and only 15 (46.9%) patients showed sensitivity. Additionally, 29 children had Entamoeba histolytica trophozoites co-infection with Salmonella on stool microscopy. Conclusions: Salmonella is more prevalent than Shigella in children under five years, while Shigella is more common in children over five. Salmonella is sensitive to both ceftriaxone and ampicillin. Shigella demonstrates resistance to multiple antibiotics, including ciprofloxacin. It is recommended that children under the age of one be admitted and treated empirically with either ceftriaxone or ampicillin. In older children, antibiotic therapy should be guided by stool culture results. Ciprofloxacin is not a good empirical choice for Shigella in our population due to its high resistance and is contraindicated in patients with glucose-6-phosphate dehydrogenase.